KATEKESE KONTEKSTUAL: SARANA DALAM MEMBANGUN GEREJA SEBAGAI UMAT ALLAH DI PAROKI ST. HILARIUS KLEPU - Stevanus Danang Setiyono; Agustinus Supriyadi (Bahasa Indonesia, 2019)
Catechesis appropriate to the situation and needs of the people is known as contextual catechesis. Catechesis of contextual context emphasizes the people "there, and that time". Under these circumstances, the formulation of the issues discussed include: What is the nature of contextual catechesis? How to build up the Church as the People of God? What contextual catechesis contribution towards efforts to build up the Church as the People of God in the Parish of St. Hilary Klepu? This research uses descriptive qualitative research method. In this qualitative study, there are 15 people who were respondents in the study. Respondents include a Pastor, catechists and parishioners in the Parish St. Hilary Klepu. Results of this study indicate that contextual catechesis has a major contribution to building the Church as the People of God in the Parish of St. Hilary Klepu. It can be seen from the implementation of catechesis contextually in Klepu social dimensions (economic, social, political, cultural, and religious). According to respondents, the Church as the People of God has also been manifested in the Parish of St. Hilary Klepu according the five tasks of the Church (fellowship, liturgy, preaching, ministry and witness), and expressions of respondents that contextual catechesis was instrumental in building the Church as the People of God in the Parish of St. Hilary Klepu.